Pediatric Treatment Scale-Up: The Unfinished Agenda of the Global Plan. (1st May 2017) - Penazzato, Martina; Amzel, Anouk; Abrams, Elaine J.; Kiragu, Karusa; Essajee, Shaffiq; Mukui, Irene; Elyanu, Peter; Rwebembera, Anath A.; Mbori-Ngacha, Dorothy
Abstract : Abstract: Five million children have died of AIDS-related causes since the beginning of the epidemic. In 2011, the Global Plan Towards the Elimination of New HIV Infections Among Children by 2015 and Keeping Their Mothers Alive (Global Plan) created the political environment to catalyze both the resources and commitment to end pediatric AIDS. Implementation and scale-up have encountered substantial hurdles, however, which have resulted in slow progress. Reasons include a lack of emphasis on testing outside of prevention of mother-to-child transmission services, an overall lack of integration and coordination with other services, a lack of training among providers, low confidence in caring for children living with HIV, and a lack of appropriate formulations for pediatric antiretrovirals. During the Global Plan period, we have learned that simplification is essential to successful decentralization, integration, and task shifting of services; that innovations require careful planning; and that the family is an important unit for delivering HIV care and treatment services. The post-Global Plan phase presents a number of noteworthy challenges that all stakeholders, national programs, and communities must tackle to guarantee universal treatment for children living with HIV. Accelerated action is essential in ensuring that HIV diagnosis and linkage to treatment happen as quickly and effectively as possible. As fewer infants are infected because of effective prevention of mother-to-child transmission interventions and the population of children living with HIV will age into adolescence adapting service delivery models to the epidemic context, and engaging the community will be critical to finding new efficiencies and allowing us to realize a true HIV-free generation—and to end AIDS by 2030.